Effect of psychosocial stress during pregnancy against prostaglandin hormone levels in maternity - Sudirman, Jumrah; Kusniyanto, Rahayu Eryanti; Saleng, Hasriani; Triananinsi, Nurhidayat; Syarif, Sutrani; Iskandar, Abdul Malik (Intelektual Pustaka Media Utama, 2023)
Stress is a mental health problem in pregnancy and affects the birthing process of breastfeeding. Stress can affect physiological processes in the body, including hormones in labor. This study evaluated the effects of stress during pregnancy on prostaglandin hormone levels in the mother during maternity. This research is an observational study using a prospective cohort approach. The number of samples in this study was 121 samples. Stress change data were analyzed using the Wilcoxon rank test and 1-way test ANOVA. The results showed there was a change in stress from first trimester to second trimester there were 23 respondents who experienced increased stress (p=0.000), second trimester to third trimester there were 102 respondents who experienced increased stress (p=0.000), and first trimester to third trimester there were 78 respondents who experienced increased stress (p=0.000). There were different prostaglandin levels based on stress levels. The mother's high stress that elevated prostaglandin levels. Stress can positively or negatively impact the processes in the mother's body, including in the delivery process effects of stress, especially on uterine contractions. Therefore, health workers can provide care by paying attention to the psychological aspects of the mother because psychological conditions can affect the processes in the mother's body.